The necessity of ESOP in the development of the stock market in Uzbekistan - Alikulov Azamat Tuygunovich; Gullieva Fayoza Bakhrom kizi (THE INNOVATION ECONOMY, 2026)
This scientific article analyzes the economic and institutional significance of introducing ESOP (Employee Stock Ownership Plan) in the development of the stock market in Uzbekistan. The study aims to identify the role of ESOP mechanisms in improving the quality of corporate governance, expanding stock market liquidity, and stimulating the investment activity of the population. Analytical and comparative methods are applied in the article, and conclusions are drawn based on international experience and the conditions of the national capital market.